Formation of City Brand in the Implementation of the Concept of Integrated Development (Economics and region, 2020)
Modern realities and requirements for sustainable development of territories need ensuring diversity and a certain identification of each city. The relevance of this process is enhanced in terms of implementing the concept of integrated urban development, so the purpose of the article is defined as a spare impact on the formation of the personal brand of the city in the process of successful implementation of integrated development planning. The development and implementation of the concept of integrated development in the cities of Ukraine significantly contributes to the formation of city branding, puts the task of developing and implementing the city brand in the foreground, and provides an opportunity to borrow successful branding experience of European cities. The result of such work is the formulation of a common vision of what the city wants to be, what and how it should achieve, the definition of strategic, operational goals and objectives, among which you can clearly trace the main directions of the city's branding. The foundations of the city's branding are laid in the most important areas of its development, as well as in the visions of the city, which create an opportunity to develop and apply your own brand.
Keywords: territory marketing; city branding; city brand; integrated development